Antidiabetic and Antioxidant Activity of Zanthoxylum armatum DC. on Type 2 Diabetic Rats: Life Science-Biochemistry - Kesavan, Keerthana; Govindasamy, Hariharan; Gurunagarajan, Sridharan; Gnanasekaran, Jothi (International Journal of Life Science and Pharma Research, 2022)
Zanthoxylum armatum DC, a medicinal plant species in India, is an exceptionally nutritious vegetable with a variety of potential uses in treating rheumatism, venomous bites, and microbial infections. In the present study, we aimed to investigated the antidiabetic and antioxidant effects of aqueous extracts of Z. armatum Stem Bark (Za-Aq) in High Fat Diet (HFD) low dose streptozotocin (STZ)-induced type 2 diabetic wistar albino rats and the objectives the were achieved through examine of blood glucose, Oral Glucose Tolerance Test (OGTT), Insulin Tolerance Test (ITT), and the levels of lipid peroxides and antioxidant enzymes, such as superoxide dismutase, glutathione peroxidase and reduced glutathione in the liver tissues of control and experimental groups. Diabetic rats were treated with 200, 400 and 800 mg/kg BW Za-Aq for 45 days and the antidiabetic effects of the extract were evaluated by measuring changes in biochemical parameters in the serum and liver tissue. Oral administration of Za-Aq to diabetic rats for 45 days significantly reduced the levels of blood glucose, OGTT, ITT and lipid peroxidation, but increased the activities of antioxidant enzymes, like superoxide dismutase, reduced glutathione and glutathione peroxidase. The progression of diabetes was significantly reduced after Za-Aq treatment. In conclusion, Za-Aq exerts protective effects against HFD-STZ-induced diabetes. The Za-Aq supplementation is useful in controlling the blood glucose level and is beneficial in preventing diabetic complications from lipid peroxidation and antioxidant systems in experimental diabetic rats; therefore, it could be useful for prevention or early treatment of diabetes mellitus active constituents may be isolated from the extract for evaluation in future clinical studies. To best of our knowledge there has been no previous comprehensive study to evaluate antidiabetic activity of stem bark from Z. armatum DC and present study adds the protective effect of Zanthoxylum armatum DC stem bark as effective antidiabetic and antioxidant agent.